2021
DOI: 10.3389/fneur.2021.613483
|View full text |Cite
|
Sign up to set email alerts
|

Patients With Becker Muscular Dystrophy Have Severe Paraspinal Muscle Involvement

Abstract: Introduction: Paraspinal muscles are important for gross motor functions. Impairment of these muscles can lead to poor postural control and ambulation difficulty. Little knowledge exists about the involvement of paraspinal muscles in Becker muscular dystrophy.Objective: In this cross-sectional study, we investigated the involvement of paraspinal muscles with quantitative trunk strength measure and quantitative muscle MRI.Methods and Materials: Eighteen patients with Becker muscular dystrophy underwent trunk, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Prior to the three maximal contractions, participants performed two practice contractions to familiarize them with the procedure. Axial muscle strength has previously been tested quantitatively in Becker muscular dystrophy 15 and LGMDR12 16 . All muscle strength tests were performed by two experienced physiotherapists (K.R., A.M.S.)…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior to the three maximal contractions, participants performed two practice contractions to familiarize them with the procedure. Axial muscle strength has previously been tested quantitatively in Becker muscular dystrophy 15 and LGMDR12 16 . All muscle strength tests were performed by two experienced physiotherapists (K.R., A.M.S.)…”
Section: Methodsmentioning
confidence: 99%
“…Grade 3: the patient was able to lift the head and sternum off the plinth with hands behind the back. 15 and LGMDR12. 16 All muscle strength tests were performed by two experienced physiotherapists (K.R., A.M.S.)…”
Section: Clinical Evaluations and Muscle Strengthmentioning
confidence: 99%
“…Whilst natural history studies in adults with BMD used to be scarce, much has been learned over the past few years. First, it was shown that muscle proton density fat fraction (PDFF) correlates strongly with a range of clinical outcome measures such as the 6-min walking distance (6MWD), North Star Ambulatory Assessment (NSAA), 32-item Motor Function Measurement scale (MFM-32) and timed-function tests in patients with BMD [5][6][7][8]. More recently, longitudinal follow-up studies have demonstrated that muscle PDFF measurements were more sensitive to change over 1-2 years than some clinical outcome measures (Biodex dynamometry, NSAA, 6MWD, 10-m run velocity) in patients with BMD [9][10][11].…”
Section: Introductionmentioning
confidence: 99%